Yowamushi pedal. 7 - Watanabe, Wataru, 1971- (Yen Press, 2017)
Day One's Shocking Climax! Team Sohoku barrels toward the end of Day One of the Inter-High...and into a neck-and-neck battle with the reigning champs, Hakone Academy! Now, Imaizumi needs to fend off the feral assault of Hakone's Arakita, and propel Kinjou to the finish line. But could Sohoku's can-do attitude also be their greatest weakness? The ever-devious Midousuji is counting on it to snatch victory!